Rosamistica - Reyes, Severino O.; Bellen, Christine S.; Flores, Liza A. (Mandaluyong City : Anvil Publishing, 2004)
A retelling of the story about a young orphan who is rewarded with coins for her kindness to a beggar woman.
Keywords: Kindness -- Juvenile fiction; Children's stories, Filipino